Knockdown of zebrafish YY1a can downregulate the phosphatidylserine (PS) receptor expression, leading to induce the abnormal brain and heart development. Issue 1 (December 2016) - Shiu, Wei-Lun; Huang, Kuan-Rong; Hung, Jo-Chi; Wu, Jen-Leih; Hong, Jiann-Ruey
Abstract Background Yin Yang 1 (YY1) is a ubiquitously expressed GLI-Kruppel zinc finger-containing transcriptional regulator. YY1 plays a fundamental role in normal biologic processes such as embryogenesis, differentiation, and cellular proliferation. YY1 effects on the genes involved in these processes are mediated via initiation, activation, or repression of transcription depending upon the context in which it binds. The role of the multifunctional transcription factor Yin Yang 1 (YY1) in tissue development is poorly understood. In the present, we investigated YY1a role in developing zebrafish on PSR-mediated apoptotic cell engulfment during organic morphogenesis. Results YY1a is first expressed 0.5 h post-fertilization (hpf), in the whole embryo 12 hpf, and in brain, eyes, and heart 72 hpf by in situ hybridization assay. The nucleotide sequence of zebrafish YY1a transcription factor (clonezfYY1a ; HQ 166834) was found to be similar to that of zebrafish YY1a (99 % sequence identity; NM 212617). With the loss-of-function assay, YY1a knockdown by a morpholino oligonucleotide led to downregulation of the phosphatidylserine engulfing receptor zfPSR during embryonic segmentation and to the accumulation of a large number of dead apoptotic cells throughout the entire early embryo, especially in the posterior area. Up to 24 hpf, these cells interfered with embryonic cell migration and cell-cell interactions that normally occur in the brain, heart, eye, and notochord. Finally, with gain-of-function assay, defective morphants could be rescued by injecting bothYY1a mRNA andPSR mRNA and trigger resumption of normal development. Conclusions Taken together, our results suggest that YY1a regulates PS receptor expression that linked to function of PSR-phagocyte mediated apoptotic cell engulfment during development, especially the development of organs such as the brain and heart. YY1a/PSR-mediated engulfing system may involve in diseases.